Pharmacies in the Airport Ecosystem and How They Serve Travelers’ Health and Medicines Need: Findings and Implications for the Future - KC B; Alrasheedy AA; Leggat PA; Molugulu N; Mohamed Ibrahim MI; Khatiwada AP; Shrestha S (Dove Medical Press, 2022)
Bhuvan KC,1,2 Alian A Alrasheedy,3 Peter A Leggat,1,2,4 Nagashekhara Molugulu,1 Mohamed Izham Mohamed Ibrahim,5 Asmita Priyadarshini Khatiwada,6 Sunil Shrestha1 1School of Pharmacy, Monash University Malaysia, Bandar Sunway, 47500, Selangor, Malaysia; 2College of Public Health, Medical and Veterinary Sciences, James Cook University, Townsville, Queensland, Australia; 3Department of Pharmacy Practice, College of Pharmacy, Qassim University, Buraidah, Qassim, Saudi Arabia; 4School of Public Health, Faculty of Health Sciences University of the Witwatersrand, Johannesburg, South Africa; 5College of Pharmacy, QU Health, Qatar University, Doha, Qatar; 6Department of Pharmaceutical and Health Service, Nepal Health Research and Innovation Foundation, Lalitpur, NepalCorrespondence: Bhuvan KCSchool of Pharmacy, Monash University Malaysia, Jalan Lagoon Selatan, Bandar Sunway, 47500, Jalan Lagoon Selatan, MalaysiaTel +603-5514 5885Email kcbhuvan@gmail.comIntroduction: Pharmacists at airport pharmacies could offer essential health services for air travelers. Consequently, this study aimed to explore the type of professional services, the types of medicines at airport pharmacies and the pharmacists' experiences and views regarding their practices.Methods: A qualitative study was conducted with pharmacists practicing in airport pharmacies from June 2020 to December 2020. A validated Google form-based interview questionnaire was developed, and the electronic link was sent to the participants. Recruitment of participants was continued until data saturation was achieved. In total, 15 pharmacists working at different airport pharmacies in different countries were included. Thematic analysis was used in the data analysis.Results: The study identified six major themes including type of professional services and medicines at airport pharmacies, pharmacists' experiences, challenges at the airport pharmacy, suggestions to improve airport pharmacy services, pandemics and the role of pharmacists, and business aspect of the airport pharmacies. The study showed that several professional services provided at airport pharmacies, including the provision of medicines, health products, general health services, travel health services, and counseling. Moreover, 46.7% of the participants reported having a dedicated travel health service. In addition, most of the participants described their experience at airport pharmacies as good and exciting as they met different people from different countries. The most common challenges that pharmacists face at airport pharmacies include language barriers, requests for different medicine brands by travelers, and financial issues. The participants indicated that there is a need for promotion of pharmacists' role in providing health care services at airport pharmacies.Conclusion: The study showed that pharmacists could play vital roles in providing medicines and health care services for air travelers. However, there is still further scope for improvement in this sector of the pharmacy profession to ensure a more active role in travel medicine.Keywords: airport pharmacy, air travel, aviation pharmacy, pharmacy services, travel health, supplements